2006
DOI: 10.1007/s00586-006-0216-7
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose aspirin before spinal surgery: results of a survey among neurosurgeons in Germany

Abstract: The main problem faced by the increasing numbers of patients presenting for spinal surgery are receiving concurrent medication with low-dose aspirin, leading to dysfunctional circulating platelets. The contribution of low-dose aspirin to increased peri-operative risk of bleeding and blood loss is a contentious issue with conflicting published results from different surgical groups. Data from neurosurgical spine patients is sparse, but aspirin has been identified as an important risk factor in the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 57 publications
(91 reference statements)
0
27
0
Order By: Relevance
“…The first group consists of procedures where any additional or excessive blood loss would lead to worse outcomes related to morbidity or mortality. 76 This group of procedures includes intracranial surgery, 77 spinal canal procedures, 78 poster chamber eye surgery, middle ear surgery, and possibly prostate surgery. The other group consists of those procedures in which an increase in surgical blood loss may have minimal consequences (no change in transfusion requirements or no increase in major morbidity or mortality).…”
Section: Surgical Bleeding and Perioperative Bleeding Complications Rmentioning
confidence: 99%
“…The first group consists of procedures where any additional or excessive blood loss would lead to worse outcomes related to morbidity or mortality. 76 This group of procedures includes intracranial surgery, 77 spinal canal procedures, 78 poster chamber eye surgery, middle ear surgery, and possibly prostate surgery. The other group consists of those procedures in which an increase in surgical blood loss may have minimal consequences (no change in transfusion requirements or no increase in major morbidity or mortality).…”
Section: Surgical Bleeding and Perioperative Bleeding Complications Rmentioning
confidence: 99%
“…Nevertheless, it is important that we did not observe significant epidural hematoma among the major complication lists. There are some studies that say that aspirin can significantly enhance such risks (16). Although spinal epidural hematoma has been reported in rare cases (13), our cases required a wider incision and a longer operation time than other studies.…”
Section: Other Factors Associated With Major Complicationsmentioning
confidence: 65%
“…Aspirin is thought to increase the risk of hemorrhage, and even a small hemorrhage can cause significant morbidity in spinal surgery. In a survey of 201 spine surgeons, two-thirds recognized that aspirin is a risk factor for excessive perioperative hemorrhage, and half of them had experienced excessive perioperative hemorrhage during surgery in patients who were taking aspirin (16). This is why spine surgeons have been reluctant to perform multi-level spine surgery on patients who are taking anti-platelet medication.…”
Section: █ Discussionmentioning
confidence: 99%
“…Aspirin has been identified as an important risk factor for postoperative bleeding and the development of hematomas including epidural hematomas in other surgical fields. [147][148][149][150][151][152] Furthermore, the use of low-dose ASA before spine surgery, even when discontinued for at least 7 days, has been suggested to lead to further blood drainage after surgery. 153 In an extensive review, low-dose ASA has also been shown to increase the rate of bleeding complications by a factor of 1.5 (median; interquartile range, 1.0-2.5).…”
Section: Procedural Recommendations: Overviewmentioning
confidence: 99%